Meta‐analysis examining the epidemiology of clozapine‐associated neutropenia. (21st May 2018) - Myles, N.; Myles, H.; Xia, S.; Large, M.; Kisely, S.; Galletly, C.; Bird, R.; Siskind, D.
Abstract : Background: Clozapine is associated with life‐threatening neutropenia. There are no previous meta‐analyses of the epidemiology of clozapine‐associated neutropenia. Objectives: To determine the cumulative incidence of mild, moderate and severe neutropenia, incidence of death related to severe neutropenia, case fatality rate of neutropenia and the longitudinal incidence of neutropenia following exposure to clozapine. Data sources: A systematic search of Medline, EMBASE and PsycINFO using search terms [clozapine OR clopine OR zaponex OR clozaril] AND [neutropenia OR agranulocytosis]. Methods: Random effects meta‐analysis to determine event rates and longitudinal incidence of events per 100 person‐years of exposure. Results: A total of 108 studies were included. The incidence of clozapine‐associated neutropenia was 3.8% (95% CI: 2.7–5.2%) and severe neutropenia 0.9% (95% CI: 0.7–1.1%). The incidence of death related to neutropenia following prescription of clozapine was 0.013% (95% CI: 0.01–0.017%). The case fatality rate of severe neutropenia was 2.1% (95% CI: 1.6–2.8%). The peak incidence of severe neutropenia occurred at one month of exposure and declined to negligible levels after one year of treatment. Conclusion: Severe neutropenia associated with clozapine is a rare event and occurs early with a substantial decline in risk after one year of exposure. Death from clozapine‐associated neutropenia is extremely rare. Implications for haematological monitoring are discussed.